Novel Treatment of Direct Carotid Cavernous Fistula with XCalibur Aneurysm Occlusion Device – A Case Report: Novel Treatment of Direct Carotid Cavernous Fistula - Ahmad, Saima; Muda, Ahmad Sobri; Rashid, Umair; Churojana , Anchalee; Mansour, Ossama Yasin (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
To report a case of post-traumatic direct carotid-cavernous fistula (CCF) treated with Merlin’s XCalibur as a standalone treatment. XCalibur is a balloon mounted flow diverter covered with polymer biostable membrane. A single device was deployed across the rent which resulted in the complete exclusion of fistula. This is the second case of its kind to be reported for the treatment of post-traumatic direct CCF with an XCalibur device. The device proved to be effective and safe and did not require any additional coiling, thus this paper has immense value and benefit for the medical community at large as it displays a new technique being successfully used.